Legal Standing of Apprentice Midwives as Health Personnels in Providing Health Services A Case Study at Health Center II of Melaya, Jembrana, Bali - Tias Rizki Ferlina; Trihoni Nalesti Dewi; Hadi Sulistyanto (Universitas Katolik Soegijapranata Semarang, 2019)
Jembrana Jembrana District was one of the Districts implementing health services through midwife apprenticeship program. One of the requirements of what so-called apprentice midwives was they who had graduated from formal education of Diploma III and Diploma IV grades. The apprentice midwives appointment was conducted by the Head of the District Health Office and it was for two-year period. During the period of apprenticeship the midwives were under the guidance of Civil Servant or Contract midwives. This study used socio-legal approach and its specification was explicative in order to view, assess and explain the relationships between the legal standing of apprentice midwife within Indonesian legal system and the legal issues appearing about the job accomplishment of the apprentice midwives. The data consisted of primary and secondary data that were then qualitatively analyzed. The results of the study showed that there was no regulation regarding the legal standing of the apprentice midwives and this made the midwives legally unprotected. Midwife apprenticeship had been carried out since 2011 but it was not a regional policy, because there was no any Regional Regulation giving a basic arrangement on it. The Head of District Health Office appointed apprentice midwives without any authority base that was granted by any legislation nor without a discretionary authority by the Regent of Jembrana. The Internship Agreement explained that the apprentice midwifes should be willing and able not to get a service fee and not demand to be appointed as Civil Servants or Contract workers of the Health Office of Jembrana District, and the Health Office of Jembrana District did not issue maternity and child birth leave letters for apprentice midwives. Besides, for the midwives as health personnels the content of the Apprenticeship Agreement was therefore contrary to the Human Rights principles because there was no basic regulations of midwife apprenticeship, the fulfillment of midwife’s rights and, from its establishment point of view, the agreement was invalid. Therefore, the apprenticeship agreement could be concluded as null and void.